Water Turnover Assessment in Overweight Adolescents - O’Connell, Bláthnaid N. (Obesity (Silver Spring), 2010)
Adequate intake (AI) standards for water in adolescents range between 2.4–3.3 l/day for males and 2.1–2.3 l/day for females, independent of obesity status. Water intakes and excretions of this population are not well documented. The purposes of this study were to assess water turnover, inputs, and outputs in overweight adolescents, compare these parameters between males and females, and evaluate the reproducibility of water turnover. Eighteen girls (BMI 31.7 ± 4 kg/m(2); mean ± s.d.) and nine boys (BMI 26.3 ± 3 kg/m(2)) aged 12–15 years completed two 3-week metabolic balance trials. Rate of water turnover (rH(2)O) was measured by tracking the decline of deuterated water from the body over 14 days. Water inputs (diet*, ad libitum(#), metabolic(#)) and outputs (urine*, feces*, insensible(#)) were assessed (*measured, #estimated). rH(2)O was lower (P = 0.002) in girls vs. boys (3,742 ± 536 vs. 4,537 ± 623 g/day). Per kg body weight, rH(2)O was 28% lower in girls vs. boys (46 ± 7 vs. 64 ± 9 g·kg(−1)·day(−1)). Water input from food and beverages provided and metabolic production were 44 and 28% lower, respectively, in girls vs. boys. Urine and insensible water losses were 21 and 17% lower in girls vs. boys. BMI was positively associated with water turnover in both sexes (girls P = 0.037; boys P = 0.014). The intraclass correlation of rH(2)O between trials was 0.981 (P < 0.001). In conclusion, these overweight adolescents consumed water well in excess of sex-specific AI standards. The lower rH(2)O in girls compared to boys is consistent with adult females and males.